Comparative Analysis of Class Reader Exercises: Approaches Of Writers - Chakrabarty, Leela (1998)
This study embarks on investigating the approaches of writers in the preparation of exercises in the Teaching files for the Class Readers. It analyses the types of exercises found in the teaching files by categorizing them into two broad categories. The findings indicate that the writers of the higher level (Form Five) teaching files prepared 'open-ended' exercises exclusively. The study also conducted a survey to find out the learners' attitude and preference towards these exercises.